A literature review exploring how health systems respond to acute shocks in fragile and conflict-affected countries - Kyaw Myat Thu; Sarah Bernays; Seye Abimbola (Conflict and Health, 2022)
Abstract Understanding how health systems respond to shocks has become a pressing need to strengthen response efforts. With already fragmented and disrupted health services, fragile and conflict affected [FCA] countries are more vulnerable to shocks. Previous studies have focused more on conceptualizing health system resilience rather than how health systems [especially in FCA countries] respond to or are resilient to acute shocks. To understand how health systems in FCA countries respond to the shocks and what influence their responses, we conducted a review of the literature published between January 2011 and September 2021 on health system responses to acute shocks in FCA countries. We searched Medline, Embase, Scopus, Jester and Google Scholar – 60 empirical studies in FCA countries on response to sudden, extreme, and unanticipated shocks were included in the review. We found that health systems in FCA countries responded to acute shock using absorptive, adaptive, or transformative capacities. These capacities were mediated by four dimensions of context; knowledge, uncertainties, interdependence, and legitimacy. In addition, we identified the cross-cutting role of community involvement [and its self-evolving nature], frontline workers, and leadership capacity. To our knowledge, this is among the first reviews that focus on FCA country health systems responses to acute shock. By highlighting enabling and constraining factors to each type of capacity, this study provides important lessons and practical strategies from FCA countries on how to absorb, adapt and transform in response to acute shocks – thus promoting health system resilience globally.